Propuesta de diseño de cuadro de mando integral para la gestión de la compañía Opsi de Colombia SAS de la ciudad de Palmira (Valle del Cauca) - Coral Cañar, Karold Jackeline; Carrillo Rengifo, John Fredy (Universidad Antonio Nariño, 2024)
The proposal to design a Comprehensive Scorecard (CMI) for the management of the company Opsi de Colombia S.A.S in the city of Palmira, Valle del Cauca, dedicated to the provision of internet services, focuses on providing a comprehensive tool that allows the company Opsi de Colombia S.A.S to effectively measure and monitor the performance and results.